Assessing artificial intelligence’s impact on e-customer loyalty in the Saudi Arabian market - Beyari, Hasan (Frontiers in Artificial Intelligence, 2025)
This study investigated the effect of artificial intelligence on e-customer loyalty in the Saudi Arabian e-commerce market. It evaluates five important variables: social media exposure, product recommendation, brand preference, purchase intention, and e-customer loyalty. The study espoused primary research methodologies by employing a questionnaire and surveying East, West, and Central Saudi Arabia. The sample size was 157 respondents, a blend of males, females, and persons of all ages. We developed a structural equation model based on six hypotheses. Ultimately, the study provided evidence that led to the confirmation of the hypotheses. We obtained credible scores in assessing the measurement model where we considered indicator reliability (0.920), internal consistency—Cronbach’s alpha (0.902), and convergent reliability – measured by Average Variance Extracted (0.765). The model fit indices indicated the model’s chi-square score was 514.355 and a CMIN/DF of 3.117. The study found that AI, particularly social media exposure and product recommendations, strongly influences Saudi e-customer loyalty. The positive association between social media exposure, purchase intention, and brand preference reveals how focused material affects customer behavior. We conclude that the model is statistically significant and that all hypotheses are supported. The implication is that artificial intelligence is a valid strategy for attaining customer loyalty on e-commerce platforms.